FORMULASI BEKATUL, IKAN GABUS DAN TEPUNG KEDELE (SOYA BUSTUL) UNTUK LANSIA - Telisa, Imelda; Meilina, Ayu; Fitriani, Ranty; Dewi, Arifah Rahma; Yasinta, Devi; Febriyansari, Dika (Jurnal Gizi, 2022)
Malnutrition in older people is brought on by a number of circumstances, including dentalissues that restrict food intake. Due to the strong connection between this issue and thenutritional status of the old, it requires careful consideration. As a result, new food productsthat are simple for the elderly to consume but provide a balanced diet are required. This studyis an experimental one conducted in a lab setting with three different treatments and acompletely randomized design. The Food Technology Science Laboratory of the NutritionDepartment of the Health Polytechnic of the Ministry of Health Palembang prepared the SoyaBustul healthy drink and conducted organoleptic tests there, while the Proximate Analysis testwas conducted at the Food Technology Laboratory, Sriwijaya University, Palembang. Thepanelists enjoyed the taste, aroma, texture, and color of the F1 treatment with the addition of25 grams of rice bran, 30 grams of snakehead fish meal, and 35 grams of soybean flour,according to the results of the organoleptic test using the hedonic scale. The overallacceptability of Soya Bustul is more despised the more snakehead fish meal, rice bran, andsoybean flour are added. The overall look of color, scent, taste, and texture has an impact onthis circumstance. The finest Soya Bustul beverage formulation has proximate analysis valuesof 5.20 percent fiber, 75.52% water, 1.10 percent ash, 3.72 percent fat, 5.84 percent protein,and 13.82 percent carbohydrates.Keyword : Elderly, Soybean, Snakehead Fish, Bran